2009
DOI: 10.1080/02841850902912010
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular ultrasound with a vector phased-array probe (acunav) is feasible in endovascular abdominal aortic aneurysm repair

Abstract: The use of AcuNav combined with fluoroscopy in EVAR was found to be safe, effective, and feasible in planning and guiding EVAR procedures. Best results were seen with the probe placed in the artery. AcuNav might be used to replace contrast-enhanced CT and angiography, hence reducing the risk of CIN, especially in high-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…This was considered preferable in order to minimize the risk of vessel trauma. The safety of the IPAI device in endovascular stentgraft procedures has been reported in an earlier study by Eriksson et al (12).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…This was considered preferable in order to minimize the risk of vessel trauma. The safety of the IPAI device in endovascular stentgraft procedures has been reported in an earlier study by Eriksson et al (12).…”
Section: Discussionmentioning
confidence: 88%
“…This makes it possible to use the probe as a fluoroscopy reference for a desired locus (12). The positioning of the radiopaque imaging elements at a specific site provided an exact localization of this point ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The phase-array elements of the probe have a characteristic fluoroscopic appearance that allows determination of the exact position of the probe. Initial analysis of the use of this catheter during endovascular aneurysm repair demonstrated that intra-arterial use of the catheter provided aortic dimensions equivalent to those determined by preoperative CT. 22 Color Doppler was able to facilitate the identification of vessel origins ( Fig 10). Endoleak identification, however, was not possible with this technology and is likely due to the direction of flow relative to the IVUS probe (due to an unfavorable Doppler angle) and due to movement artifacts in the aneurysm sac.…”
Section: Intravascular Ultrasoundmentioning
confidence: 99%
“…Commercial 2D ultrasound catheters may also be applied for device guidance. One group has reported the use of an AcuNav (Siemens, Mountain View, CA) ultrasound probe for the planning and guiding of an endovascular aneurysm repair (EVAR) 1. This was combined with fluoroscopy.…”
Section: Introductionmentioning
confidence: 99%